2012
DOI: 10.1016/j.jpeds.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Urine Biomarkers Predict Acute Kidney Injury in Newborns

Abstract: Objective To identify urine biomarkers predictive of acute kidney injury (AKI) in infants admitted to level 2 and 3 neonatal intensive care units with birth weight >2000 g and 5-minute Apgar score ≤7. Study design A nested case-control study was performed comparing 8 candidate urine AKI biomarkers in infants with AKI (defined as a rise in serum creatinine of at least 0.3 mg/dL or a serum creatinine elevation ≥1.7 mg/dL persisting for 3 days) and 24 infants from the described cohort without AKI. Urine was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 38 publications
3
77
3
2
Order By: Relevance
“…[132][133][134] Biomarkers including urine cystatin C, uromodulin, epithelial growth factor, neutrophil gelatinase-associated lipocalin, and osteopontin predict AKI in specific neonatal populations. 135,136 …”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…[132][133][134] Biomarkers including urine cystatin C, uromodulin, epithelial growth factor, neutrophil gelatinase-associated lipocalin, and osteopontin predict AKI in specific neonatal populations. 135,136 …”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Although we believe that the AKI definition used here is the best definition of AKI currently available for asphyxiated infants receiving therapeutic hypothermia, the AKI-staging criteria may yet be imprecise with substantial severity overlap (especially between stages 2 and 3) and may poorly stratify outcomes. Future studies using novel biomarkers of kidney function that have been shown to be more precise in the neonatal period may allow for more precise definitions of AKI (18). Limitations of the descriptions of the MRI categories may also be another reason for the lack of correlation between AKI and the MRI findings.…”
Section: Kidney Injury Brain Mri and Coolingmentioning
confidence: 99%
“…The value of NGAL in pediatric field of medicine was most assessed in kidney injury states. Askenazi in 2 nested case-control studies on very low birth weight and normal weight neonates found that urinary level of NGAL was higher in neonates with acute kidney injury compared with normal ones (17)(18).Recently, a few investigations were performed to evaluate such levels in obstructive hydronephrotic children. Mia Gebauer Madsen et al, in a study on children suffered from ureteropelvic junction obstruction, evaluated NGAL levels in preoperative, perioperative, and postoperative periods and found a significant increased of NGAL in the perioperative urine compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%